2014
DOI: 10.4049/jimmunol.1300148
|View full text |Cite
|
Sign up to set email alerts
|

NKT Cells Determine Titer and Subtype Profile of Virus-Specific IgG Antibodies during Herpes Simplex Virus Infection

Abstract: Invariant NKT cells (iNKT cells) are innate lymphocytes that recognize lipid-derived Ags presented by the MHC class I–related protein CD1d. In this study, we analyzed the role of iNKT cells in the generation of Abs against HSV type 1 (HSV-1). In sera from healthy hman donors, we found a correlation between HSV-1–specific IgG titers and proportions of CD4+ iNKT cells. In HSV-1–infected iNKT cell–deficient mice, the amount of specific IgM and IgG Abs were significantly reduced compared with wild-type mice. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Here, we found that virus-specific IgG2b and IgG2c antibodies also inflate during persistent MCMV infection, and that the degree of antibody inflation relates to the dose of the initial viral inoculum. In other persistent infections, such as chronic lymphocytic choriomeningitis virus (LCMV) (25,26) or herpes simplex virus infection (27), virus-specific antibodies also accumulate with time, albeit to various degrees. However, the serum levels of these virus-specific IgG antibodies eventually decline.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that virus-specific IgG2b and IgG2c antibodies also inflate during persistent MCMV infection, and that the degree of antibody inflation relates to the dose of the initial viral inoculum. In other persistent infections, such as chronic lymphocytic choriomeningitis virus (LCMV) (25,26) or herpes simplex virus infection (27), virus-specific antibodies also accumulate with time, albeit to various degrees. However, the serum levels of these virus-specific IgG antibodies eventually decline.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of virus-specific IgM and IgG is significantly reduced in iNKT cell-deficient mice compared to their wild-type counterparts [74]. Furthermore, iNKT cells are relevant in shaping the IgG subtype profile of HSV-1-specific Abs, as IgG2c and IgG3 Abs are barely detectable in Jα18 −/− mice compared to WT animals [74]. This deficit results from insufficient IFNγ production that promotes the switch to IgG2c and IgG3, suggesting that iNKT cells are required for HSV-1-induced IFNγ production [74].…”
Section: Spontaneous Inkt Cell Help To B Cellsmentioning
confidence: 94%
“…iNKT cell help to B cells may occur also in a spontaneous manner, that is to say in the absence of αGalCer, as it was demonstrated by investigating the role of iNKT cells in HSV-1-induced B cell responses [74]. The amount of virus-specific IgM and IgG is significantly reduced in iNKT cell-deficient mice compared to their wild-type counterparts [74].…”
Section: Spontaneous Inkt Cell Help To B Cellsmentioning
confidence: 99%
See 2 more Smart Citations